THE ROLE OF DECISION SUPPORT SYSTEMS CENTERS TO ENHANCE ADMINISTRATIVE REFORM IN PUBLIC INSTITUTIONS - EXPLORATORY STUDY IN IRAQI PUBLIC INSTITUTIONS - Fadi Hassan Jaber (Scholar Express Journals, 2022)
The research identifies the importance of having a decision support system center that consists of academics, experts, and specialists in finding solutions to achieve administrative reform, which contributes to determining requirements and evaluation to support the process of administrative reform in public institutions. The study examines the lack of public institutions of the advisory and supervisory in achieving reform. In addition to the absence of vision management that aimed to identify problems and find innovative solutions to crisis Chaos and paradox that diagnosis in institutions. That required Solutions based on stability or change in the organizational life of institutions. Sample of 43 academics and managers working in public institutions and used method of statistical analysis depending on SPSS V. 23 analyze the results. This showed the vital and effective role of the decision support center in achieving administrative reform. Additionally, the study represented recommendations That advise establishing a center support decision contributes to the completion of administrative reform in Iraqi public institutions
Keywords: institutions; public; Iraqi; establishing